2011
DOI: 10.1515/bc.2011.200
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of human 5-lipoxygenase

Abstract: Human 5-lipoxygenase (5-LO) can form dimers as shown here via native gel electrophoresis, gel fi ltration chromatography and LILBID (laser induced liquid bead ion desorption) mass spectrometry. After glutathionylation of 5-LO by diamide/glutathione treatment, dimeric 5-LO was no longer detectable and 5-LO almost exclusively exists in the monomeric form which showed full catalytic activity. Incubation of 5-LO with diamide alone led to a disulfi debridged dimer and to oligomer formation which displays a strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 64 publications
3
38
0
Order By: Relevance
“…Wild-type and C418S mutant (replacement of Cys418 to serine) 5-LO were purified by anion exchange chromatography as previously described (3,14) and used for the quantification of the iron content. Equal amounts (30 ng/reaction) of enzymes were incubated with solvent (1& DMSO), 5 lM of OA, LA, NO 2 -OA, or NO 2 -LA for 15 min, dialyzed overnight (Slide-A-Lyzer G2 dialysis cassette; Thermo Scientific) before HNO 3 (0.015 M final concentration) was added to each sample.…”
Section: Iron Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type and C418S mutant (replacement of Cys418 to serine) 5-LO were purified by anion exchange chromatography as previously described (3,14) and used for the quantification of the iron content. Equal amounts (30 ng/reaction) of enzymes were incubated with solvent (1& DMSO), 5 lM of OA, LA, NO 2 -OA, or NO 2 -LA for 15 min, dialyzed overnight (Slide-A-Lyzer G2 dialysis cassette; Thermo Scientific) before HNO 3 (0.015 M final concentration) was added to each sample.…”
Section: Iron Determinationmentioning
confidence: 99%
“…The histidine residues modified in the 5-LO are conserved in the human platelet-type 12-LO and 15-LO-1 enzymes that are resistant to NO 2 -FA inhibition, inferring that the adduction of histidine residues alone could not account for preferential inhibition of 5-LO by NO 2 -FA. Cysteines at positions 159, 300, 416, and 418 are, on the other hand, unique to 5-LO; they are also located at the solvent interface of the enzyme and critical for enzymatic activity (14). The 5-LO tryptic peptide containing Cys416 and Cys418 was alkylated after incubation with NO 2 -OA (Table 2), and mass spectrometric analysis revealed that both cysteine residues were modified ( Fig.…”
mentioning
confidence: 99%
“…In silico phosphorylation of human 5-LO For visual inspection of the newly identified phosphorylation sites, a model of the human 5-LO crystal structure (Protein Data Bank, http://pdb.org [26]), Database ID 3o8y [40], was used as described previously [41]. Visualization was performed using PYMOL version 0.99rc6 (http://www.py mol.org/).…”
Section: Maldi-ms Analysismentioning
confidence: 99%
“…25 Lastly, the ability of 5-LOX to dimerize may provide yet another avenue of enzymatic regulation. 26 …”
mentioning
confidence: 99%